2021
DOI: 10.1002/ece3.8440
|View full text |Cite
|
Sign up to set email alerts
|

Seed traits matter—Endozoochoric dispersal through a pervasive mobile linker

Abstract: Although many plants are dispersed by wind and seeds can travel long distances across unsuitable matrix areas, a large proportion relies on co‐evolved zoochorous seed dispersal to connect populations in isolated habitat islands. Particularly in agricultural landscapes, where remaining habitat patches are often very small and highly isolated, mobile linkers as zoochorous seed dispersers are critical for the population dynamics of numerous plant species. However, knowledge about the quali‐ or quantification of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…The effects of these features could be better explained by a non-linear smooth function. For instance, it is not plausible that temperature has a linear effect on acceleration of hares since it is natural to expect less movement at extreme temperatures (Stiegler et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of these features could be better explained by a non-linear smooth function. For instance, it is not plausible that temperature has a linear effect on acceleration of hares since it is natural to expect less movement at extreme temperatures (Stiegler et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of empirical data found that species that are strictly diurnal are much likelier than temporally flexible species to have already displayed range shifts or contractions in response to climate change (McCain & King, 2014), and metabolic niche modeling has indicated that small diurnal mammals are disproportionately likely to lose habitat due to future warming (Bonebrake et al., 2020). Species' behavioral responses to temperatures above their optimal range will be highly important in predicting future range shifts (Levy et al., 2019; Thurman et al., 2020), as well as changes to reproductive behaviors (Sharpe et al., 2019; Stiegler et al., 2023) and interspecific interactions (Traill et al., 2010). However, for many species, the impact of environmental temperatures on behavior remains unknown (Fuller et al., 2016; Levy et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The passage of seeds through the digestive tract of the animal is a critical phase in endozoochory because the survival of seeds in the digestive system is one of the main determinants of the success of endozoochorous dispersal. Complex interactions are, therefore, established between the characteristics of the animals and plants for their survival in the digestive tract (Cosyns et al, 2005 ; Stiegler et al, 2021 ). To understand how mammalian handling and gut passage affect seeds; for example, viability and scarification, it is essential to conduct seed‐feeding experiments under controlled experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to take into consideration that the variability that exists between plants and animals means that seed‐feeding experiments can present contrasting results, with greater germination success found in some cases (Grande et al, 2013 ; Mancilla‐Leytón et al, 2011 ) and lower success in others (D'hondt & Hoffmann, 2011 ; Grande et al, 2013 ). The potential for endozoochorous dispersal in many plant species has been evaluated using seed‐feeding experiments, particularly with herbivores (Poulsen et al, 2021 ; Sadeghayobi et al, 2011 ; Wang et al, 2017 ) such as domestic rabbits, sheep, and cows (Cosyns et al, 2005 ) or by the germination testing of collected scat samples (Milotić & Hoffmann, 2016 ; Salinas & Reynoso, 2023 ; Stiegler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%